Peran Profitabilitas Sebagai Mediasi Dalam Hubungan Struktur Modal, Kesempatan Investasi dan Kebijakan Dividen Terhadap Nilai Perusahaan Sub Sektor Industri Kelapa Sawit Periodem 2018-2023 - zairi, zairi; Sahroni, Sahroni; Sampurnaningsih, Sri Retnaning (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze the effect of capital structure, investment opportunity, and dividend policy on firm value with profitability as a mediating variable in palm oil sub-sector companies listed on the Indonesia Stock Exchange during 2018–2023. The background of this research is based on the fluctuations in financial performance reflected in firm value, profitability, and financial policies, as well as inconsistent findings in previous studies. This research employs a quantitative approach using panel data regression analysis. The sample was determined through purposive sampling and consists of 10 companies with a total of 60 observations. The data were obtained from annual financial statements and stock price information published by the Indonesia Stock Exchange. The results show that capital structure, investment opportunity, and dividend policy do not have a significant effect on profitability. Investment opportunity has a positive and significant effect on firm value, while capital structure, dividend policy, and profitability have no significant effect. Furthermore, profitability does not mediate the relationship between the independent variables and firm value. These findings indicate that investors place greater emphasis on long-term growth prospects rather than short-term profitability or financing policies when assessing palm oil companies. The study implies the importance of sustainable growth strategies in enhancing firm value and opens opportunities for further research by including external factors such as global commodity prices and environmental issues.